Fat and Lean Mass Predict Bone Mass During Energy Restriction in Sedentary and Exercising Rodents - Metzger, Corinne E.; Swift, Sibyl N.; Baek, Kyunghwa; De Souza, Mary Jane; Bloomfield, Susan A. (Frontiers in Physiology, 2018)
Energy restriction (ER) causes bone loss, but the impact of exercise during ER is less understood. In this study, we examined the impact of metabolic hormones and body composition on both total body bone mineral content (BMC) and local (proximal tibia) volumetric bone mineral density (vBMD) during short- (4 wk) and long-term (12 wk) ER with and without exercise in adult female rats. Our first goal was to balance energy between sedentary and exercising groups to determine the impact of exercise during ER. Secondly, we aimed to determine the strongest predictors of bone outcomes during ER with energy-matched exercising groups. Methods: Female Sprague Dawley rats were divided into 3 sedentary groups (ad libitum, -20% ER, -40%) and 3 exercising groups (ad libitum, -10% ER, and -30% ER). Approximately a 10% increase in energy expenditure was achieved via moderate treadmill running (~60-100 min 4 day/week) in EX groups. n per group = 25-35. Data were analyzed as a 2x3 ANOVA with multiple linear regression to predict bone mass outcomes. Results: At 4 wks, fat and lean mass and serum insulin-like growth factor-I (IGF-I) predicted total body BMC (R2=.538). Fat mass decreased with ER at all levels, while lean mass was not altered. Serum IGF-I declined in the most severe ER groups (-40% and -30%). At 12 wks, only fat and lean mass predicted total body BMC (R2=.718). Fat mass declined with ER level regardless of exercise status and lean mass increased due to exercise (+5.6-6.7% vs. energy-matched sedentary groups). At the same time point, BMC declined with ER, but increased with exercise (+7.0-12.5% vs. energy-matched sedentary groups). None of our models predicted vBMD at the proximal tibia at either time point. Conclusion: Both fat and lean mass statistically predicted total body BMC during both short- and long-term ER. Fat and lean mass decreased with ER, while lean mass increased with EX at each energy level. Measures that predicted total body skeletal changes did not predict site-specific changes. These data highlight the importance of maintaining lean mass through exercise during periods of energy restriction.